Concept mapping as a tool to facilitate clinical reasoning in complex multimorbidity cases in undergraduate Primary Care curricula - Fonseca, Marta (2025)
Introduction This thesis begins by outlining the four central themes of the project: clinical reasoning and critical thinking, the use of concept maps (CMs) in medical education, multimorbidity in Family Medicine, and undergraduate medical education (UME). It emphasizes the importance of clinical reasoning in UME, defined as a skill, a process and an outcome, as it remains the cornerstone of medical practice. However, clinical reasoning is often poorly understood and challenging to teach and assess due to its complexity and multidimensional nature. The thesis also highlights the use of CMs as a pedagogical tool designed to facilitate knowledge integration and critical thinking. While CMs have been widely used to enhance learning outcomes, their role in transitioning from basic sciences to clinical practice, particularly in managing multimorbidity, remains underexplored. Multimorbidity, a daily challenge in Family Medicine, adds complexity to patient care and underscores the need for effective clinical reasoning training. This project focuses on the development, implementation, and evaluation of a CM-based intervention to facilitate clinical reasoning for fifth-year medical students during their Family Medicine clerkship. The main research question is whether concept mapping, compared with traditional teaching methods, facilitates clinical reasoning in undergraduate medical students using clinical vignettes of multimorbidity patients.Methods This action research project was grounded in an interpretivist approach, following a cyclical process of implementing a pedagogical tool, collecting data, and engaging in reflective analysis. It consisted of three components: a literature review, an exploratory qualitative study, and a large-scale implementation study. The systematic review employed a mixed-methods approach to answer the questions: 'What studies have been published on concept mapping in UME?', 'What was the impact of CMs on students’ critical thinking?', and 'How and why have these interventions had an educational impact?'. A study protocol was completed a priori and uploaded to the study repository on the Best Evidence Medical Education (BEME) website. The search was conducted across eight databases, from their inception until May 2022, with an updated search performed in March 2023. We reported the results following the STructured apprOach to the Reporting In healthcare education of Evidence Synthesis (STORIES) statement and BEME guidance. The exploratory qualitative study aimed to understand how CMs could facilitate clinical reasoning in multimorbidity patients within undergraduate Family Medicine curricula in our local context, as perceived by both students and tutors. It also sought to explore the implementation process, and the resources required. We conducted a qualitative evaluation of the intervention sessions, students’ group interviews, and a focus group with family physician tutors. The large-scale implementation study employed a mixed-methods approach in a controlled, non-randomized design. Students were assigned to sessions using either CMs or traditional methods (TM). Quantitative data were collected through a feedback questionnaire and the evaluation of an individual task, while qualitative data included responses to an open-ended question and an analysis of the individual task. Results The BEME review included 39 studies from 26 journals. CMs were identified as effective teaching and learning tools that helped developing critical thinking, as perceived by both students and tutors, as well as in assessments of students' knowledge and skills. This effectiveness was attributed to the flexibility of CMs in facilitating knowledge integration, functioning as both a learning and teaching method. The wide range of contexts, purposes, and variations in how CMs and critical thinking assessment tools were employed further increased our confidence in the consistency of these positive effects. The exploratory qualitative study identified three main educational impacts: integration of clinical information, support for patient management and treatment plan, and collaborative learning. CMs proved to be effective tools that helped students better understand patients with multimorbidity and promoted key components of clinical reasoning, such as problem representation and support for management and treatment plan. Key aspects for successful CM implementation included providing clear instructions and sufficient time for CM construction, utilizing user-friendly software, encouraging group discussions, and incorporating tutor feedback. The large-scale implementation study found no definitive evidence supporting the superiority of CMs over TMs; however, promising trends were noted. The CM group demonstrated improved performance in individual tasks and better organization in managing multimorbidity cases. ConclusionsThis research successfully developed, implemented, and evaluated a CM-based intervention aimed at promoting clinical reasoning in managing clinical vignettes of multimorbidity patients within the undergraduate Family Medicine curriculum. Findings demonstrated the value of CMs as pedagogical tools that stimulate higher metacognitive functioning in medical students, allowing them to connect basic sciences with clinical concepts, through a visual representation of knowledge. This approach promoted reflective thinking and clinical reasoning in the management of multimorbidity. Although the study did not definitively prove the superiority of CMs over TMs, promising trends suggested potential benefits. The intervention provided a framework for addressing multimorbidity, a key challenge in Family Medicine, and underscored the importance of incorporating CMs throughout medical education. This approach could equip future general practitioners with essential tools for clinical reasoning, while also contributing to the advancement of medical education in Portugal. Although further research is needed to refine the interventions and assessment methods and to better understand the long-term impact of CMs, this project makes a solid contribution to the implementation of innovative teaching strategies in medical education.